Stifle kinematics in 4 dogs with cranial cruciate ligament insufficiency treated by CORA-based leveling osteotomy - Tinga, Selena; Hughes, Natalie; Jones, Stephen C.; Park, Brian; Palm, Lindsey; Desaraju, Sasank S.; Banks, Scott A.; MacArthur, Sandra L.; Lewis, Daniel D. (Frontiers in Veterinary Science, 2022)
Objective The purpose of this study was to quantify three-dimensional (3D) stifle kinematics during walking in dogs with complete cranial cruciate ligament insufficiency (CCL-I) treated with a CORA-based leveling osteotomy (CBLO). Study design Four client-owned dogs with unilateral complete CCL-I were prospectively enrolled. Custom digital 3D models of the femora and tibiae were created from pre-and postoperative computed tomographic scans for each dog. Lateral view fluoroscopic images were collected during treadmill walking preoperatively and 6 months after CBLO. Results were generated using a 3D-to-2D image registration process. Pre-and postoperative stifle kinematics (craniocaudal translation, extension angle) were compared to that of the unaffected contralateral (control) stifle. Force plate gait analysis was performed, and symmetry indices (SI) were calculated for peak vertical force (PVF) and vertical impulse (VI). Results After CBLO, craniocaudal femorotibial motion was reduced by a median (range) of 43.0 (17.0–52.6) % over the complete gait cycle. Median (range) PVF SI was 0.49 (0.26–0.56) preoperatively and 0.92 (0.86–1.00) postoperatively, and VI SI was 0.44 (0.20–0.48) preoperatively and 0.92 (0.82–0.99) postoperatively. Conclusion CBLO mitigated but did not fully resolve abnormal craniocaudal translation; lameness was substantially improved at 6 months.